Sanders type IIIAB calcaneal fracture without broken lateral wall: A case report and review of literature. Issue 7 (February 2018) - Yue, Zhenshuang; Tang, Yanghua; Hu, Zhongqing; Zheng, Wenjie
Abstract: Rationale: The calcaneal fracture without broken lateral wall is rare and the open anatomic reduction and internal fixation (ORIF) is necessary when the subtalar joint articular surface is broken and collapsed. Patient concerns: A 45-year-old male was admitted to our department with complaints of heel pain and swelling after falling down from 1-m-high stone. He was unable to bear weight on his right foot. Diagnoses: Imaging studies confirmed that it was a sanders type IIIAB calcaneal fracture without broken lateral wall and the middle part of the posterior calcaneal articular facet collapsed. Interventions: ORIF of intraarticular calcaneal fracture with the locking calcaneal plate was performed. Outcomes: The patient recovered completely after 16 weeks and was able to participate in his usual work. Lessons: Based on this case and literature we reviewed, computed tomography scan (CT scan) should be used to diagnose and evaluate the severity of calcaneal fractures. Currently, ORIF was the preferred surgical treatment option when dealing with displaced intraarticular calcaneal fractures.